Определение семантической близости на основе когнитивного подхода - Хайрова, Нина Феликсовна; Шаронова, Наталья Валерьевна; Борисова, Наталья Владимировна (Харківський національний університет радіоелектроніки, 2013)
Предлагается логическая схема выделения семантических эквивалентов, основанная на формализации когнитивной и номинативной функции языка. Формализация осуществляется за счет факторизации пространства концептов. Доказывается возможность использования подходов и методов теории интеллекта для реализации данной схемы в формальных моделях на языке логики предикатов. Вводятся предикаты эквивалентности, разбивающие множество лингвистических единиц на классы общего категориального значения.

In the paper, we suggest logic scheme for semantic equivalence identification based on the formalization of cognitive and nominative language functions. The formalization is based on the factorization of space concepts. We prove a possibility of using approaches and methods of theory of intelligence for implementation the logic scheme in formal models in the language of predicate logic. Moreover, we provide predicates of equivalence for partitioning of the set of the linguistic units with regard to the defined categorical value.
Identification of semantic proximity based on the cognitive approach
Keywords: когнитивная семантика; семантические эквиваленты; теория интеллекта; логика предикатов